The Roles of Geographical Study in Spatial Arragement and Regional Development (A Case Study in Sukoharjo District) - Priyono, Kuswaji Dwi; Kaeksi, Retno Woro (Forum Geografi, 1996)
The following issue explains the role of geography study in spatial lay-out and regional development, taking the regional development of Sukoharjo regency as the case study. The role of geography study in spatial lay-out and regional development lies mainly in the effort to achieve geo information system, i.e. information of regional landscape with its all characteristics, regional problem, regional development potential and the definitive factor of regional development. Making use of geography analysis, Sukoharjo as a brief out line has three geomorphology units with its different physic potential and soial economy, and up to the present it has a tendency of different land function. The three units of geomorphology mention above are: alluvial plain, fluvio-volcanic foot plain of Lawu, and shouthern hill slope of Baturagung. And then, to support the area development of JOGLOSEMAR the future development strategies of Sukoharjo regency is distinguished into three zones, i.e.: industry and comercial zone, urban residential and institution zone, open sphere land and recreation zone.